2015
DOI: 10.1007/s11440-015-0415-7
|View full text |Cite
|
Sign up to set email alerts
|

A hypoplastic macroelement for single vertical piles in sand subject to three-dimensional loading conditions

Abstract: International audienceThis paper presents a novel macroelement for single vertical piles in sand developed within the hypoplasticity theory, where the incremental nonlinear constitutive equations are defined in terms of generalized forces, displacements and rotations. Inspired from the macroelement for shallow foundations of Salciarini and Tamagnini [Acta Geotechnica, 4(3):163--176, 2009], the new element adopts the intergranular displacement mutuated from Niemunis and Herle [Mechanics of Cohesive--Frictional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 54 publications
(76 reference statements)
0
57
0
Order By: Relevance
“…Its simplicity and robustness make it an ideal basic model to build more sophisticated models, e.g., critical state model and high-order model [5,8,9,13,30,31]. The failure surface is derived from the constitutive equation and likes that of DruckerPrager.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its simplicity and robustness make it an ideal basic model to build more sophisticated models, e.g., critical state model and high-order model [5,8,9,13,30,31]. The failure surface is derived from the constitutive equation and likes that of DruckerPrager.…”
Section: Discussionmentioning
confidence: 99%
“…In general, c 3 assumes different values in (6) and (8). The performance of (8) [20] used a different set of material parameters, which can be related to the three material parameters E i , m i and / crt .…”
Section: Basic Model: From Wu To Wolffersdorffmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that the model (21) is applicable to both initially and fully developed plastic deformation of granular materials with drained or undrained conditions [41,43]. It will reduce to the original one (16) when the void ratio e is equal to the critical value e crt from (22) and (23). It means, for same material, same constants c 1 $ c 4 will be obtained for the original and extended models in the case of e ¼ e ecrt .…”
Section: Introductionmentioning
confidence: 95%
“…Recently some improved models have been available, e.g. [12,23,35], which are developed from some widely used versions of hypoplastic model [28,37] and aim to improve the dependence of stiffness on pressure and density. However, the capability of these models for capturing the phenomenon of liquefaction and the stability in the cases of large deformation or low confining pressure still need to be verified.…”
Section: Introductionmentioning
confidence: 99%